Environmental regulations and business decisions - Wayne B. Gray (IZA World of Labor, 2015)
Environmental regulations raise production costs at regulated firms, though in most cases the costs are only a small fraction of a firm's total costs. Productivity tends to fall, and firms may shift new investment and production to locations with less stringent regulation. However, environmental regulations have had enormous benefits in terms of lives saved and illnesses averted, especially through reductions in airborne particulates. The potential health gains may be even greater in developing countries, where pollution levels are high. The benefits to society from environmental regulation hence appear to be much larger than the costs of compliance.
Keywords: Q52; Q58; 330; regulation; productivity; plant location; pollution abatement costs